System-Based Education Quality Management: Challenges and Opportunities - Subni, Muhammad; Fitrianti, Fitrianti; Azainil, Azainil (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The system-based educational quality management approach enables the optimal enhancement of educational quality through the integration and synergy of various educational elements. This study explores the strategic planning, organization, implementation, and monitoring of the system-based quality management approach in primary schools. The research addresses key challenges such as resistance to change and limited resources, providing solutions like stakeholder involvement, the use of information technology, and structured change management. Core elements of this approach include curriculum design, innovative teaching methods, competent human resources, and adequate educational facilities. The approach promises significant benefits, including operational efficiency, improved student learning outcomes, and enhanced institutional reputation and competitiveness. By understanding and overcoming challenges while leveraging opportunities, educational institutions can achieve sustainable quality improvements and create supportive learning environments that facilitate high student achievement.